Radio Broadcasting Innovation Management, Digital Technology Enhances Excellence Radio Business Performance - Elfani Prasetyaningrum, Nurita; Agus Triono Sudalyo, Ramadhian; Kusanti, Jani (GEMA EKONOMI, 2023)
Development is carried out by mapping based on the potential of each district. However, the potential of its natural resources has not been optimally explored for industrial opportunities due to the absence of supporting maintenance. The results show that most of the potential is in its natural resources. Market opportunities usually meet the interests of individuals, such as brokers who create the largest profit margins. On the other hand, the craft community collects very minimal profits. In fact, human resources have enormous potential but become a problem when there is no regeneration of the younger generation. In addition, corporate institutional factors are needed to increase the potential bargaining position of the d